Study of the Relationship between the Level of Lubricating Oil Contamination with Distillation Fuel and the Risk of Explosion in the Crankcase of a Marine Trunk Type Engine - Leszek Chybowski (Energies, 2023)
Fuel contamination of engine lubricating oil has been previously determined to arise from two independent phenomena: the effect on oil flash point, and the effect of changing lubrication conditions on tribological pairs. This paper combines these effects and holistically analyzes the consequences of fuel in the lubricating oil of a trunk piston engine on the risk of crankcase explosion. The author hypothesized that diesel fuel as an oil contaminant increases the risk of an explosion in the crankcase of an engine due to the independent interaction of two factors: (1) changes in the oil’s combustible properties, and (2) deterioration of the lubrication conditions of the engine’s tribological nodes, such as main bearings, piston pins, or crank bearings. An experiment was performed to evaluate the rheological, ignition, and lubrication properties of two oils (SAE 30 and SAE 40) commonly used for the recirculation lubrication of marine trunk piston engines for different levels of diesel contamination. The hypothesis was partially confirmed, and the results show that contamination of the lubricating oil with diesel fuel in an amount of no more than 10% does not significantly affect the risk of explosion in the crankcase. However, diesel concentrations above 10% call for corrective action because the viscosity index, lubricity, coefficient of friction and oil film resistance change significantly. Deterioration of the tribological conditions of the engine bearings, as seen in the change in viscosity, viscosity index, and lubricity of the oil, causes an increase in bearing temperature and the possibility of hot spots leading to crankcase explosion.